Risk of Stillbirth in Women with Gestational Diabetes and High Blood Pressure - Hamid Reza TABATABAEE; Atefeh ZAHEDI; Koorosh ETEMAD; Tannaz VALADBEIGI; Sepideh MAHDAVI; Mostafa ENAYATRAD; Seideh Zeinab ALMASI; Halime YAGHOOBI; Fatemeh ZOLFIZADEH; Mahmoud HAJIPOUR (Tehran University of Medical Sciences, 2020)
Background: Both Gestational diabetes and hypertension almost affect 10.5% of the pregnancies. This study was conducted to investigate and compare the pregnancy outcomes in women with gestational diabetes or high blood pressure with outcomes belonging to healthy mothers. Methods: This population-based case-control study was conducted in 8 provinces and two cities of Iran on women referred to the public health centers during 2015 to 2018. Descriptive statistics for variables presented by percentages and frequencies and logistic regression analysis was used to analyze data at a significance level of less than 0.05. Results: Some variables such as ethnicity, maternal education and age, gestational diabetes, high blood pressure and previous pregnancy outcome were significantly associated with stillbirth. Maternal age greater than 35 yr (OR=1.78, CI: 1.29-2.48), maternal illiteracy (OR=3.67, CI: 2.25-5.98), a previous stillbirth (OR=9.92, CI: 4.98-19.78), gestational diabetes among women who had never had a screening test (OR =3.91, CI: 2.96-5.18) and high blood pressure (OR =1.95, CI: 1.38-2.77) were important factors associated with stillbirth. Maternal and paternal occupation, paternal education and age, place of residence, smoking and maternal BMI were significantly associated with stillbirth. Conclusion: Gestational diabetes, hypertension, a previous miscarriage, stillbirth, first pregnancy, low education level, advanced maternal age and ethnicity were associated with an increased risk of stillbirth. It is necessary to provide high-quality healthcare services before and during pregnancy particularly for those at heightened risk and improve knowledge of mothers on the side effects of each of the mentioned risk factors in order to control these factors more effectively and thus reducing the risk of stillbirth.